Odpowiedzi

2009-11-19T21:25:23+01:00
B)

wzór:
y = 2x - 1

więc:
y = 2 * 4 - 1 = 8 - 1 = 7

:))
Najlepsza Odpowiedź!
2009-11-19T21:41:11+01:00
A) oblicz f(√3-4) i przedstaw tę wartość w postaci a+b√3, gdzie a i b są liczbami wymiernymi
x = √3-4
f(√3-4) = |(1-√3-4)²-5|
f(√3-4) = |(-3-√3)²-5|
f(√3-4) = |9+6√3+3-5|
f(√3-4) = |6√3+7|
y = 6√3+7 ∨ y = -6√3-7

y = 7+6√3 ∨ y = -(7+6√3)

b) oblicz x, jeśli wiadomo, że f(x)=4

f(x) = |(1-x)²-5|
f(x) = |1-2x+x²-5|
f(x) = |x²+2x-4|
f(x) = 4
|x²+2x-4| = 4
x²+2x-4 = 4 ∨ x²+2x-4 = -4
x²+2x-8 = 0 ∨ x²+2x = 0

x²+2x-8 = 0
Δ = b²-4ac = 4+32 = 36 => √Δ=6

x₁=(-b-√Δ)/2a ∨ x₂=(-b+√Δ)/2a
x₁=(-2-6)/2 ∨ x₂=(-2+6)/2
x₁=-4 ∨ x₂=2

x²+2x = 0
x(x+2) = 0
x=0 ∨ x+2=0
x=0 ∨ x=-2

odp: x₁=-4 ∨ x₂=2 ∨ x=0 ∨ x=-2
x∈{-4,-2,2,0}